Synthesis and Characterization of N-Substituted Tetrahydroiso-quinoline Derivatives via a Pictet-Spengler Condensation - Patel, Heta A.; Patel, Arun L. (Journal of Applied Solution Chemistry and Modeling, 2014)
Synthesis of N-substituted 1,2,3,4 –tetrahydroisoquinoline derivatives and bis-isoquinoline has been carried out via a Pictet-Spengler condensation. Tetrahydroisoquinolines were obtained from 2-(3',4'-dimethoxyphenyl) ethylamine in four steps. The entire synthesized compounds were characterized by IR, 1H NMR and mass spectral data.